Report of cases of anorectal injuries caused by knives or sharp objects leading to death in Soacha, Colombia, 2015 (2016)
Purpose: The purpose of this review to inform the authorities and the scientific community a series of murders with similar circumstances suggesting the same modus operandi. Topic: Serial killings among vulnerable population with evidence of torture and impalement. Development: A review is made of three cases of adult men, alleged substance abusers with signs suggesting torture, injured by sharp objects in the anorectal region; this in contrast to the cadaver of a male victim, who showed signs of blunt trauma with evidence of anal penetration maneuvers. Conclusions: The full legal medical study establishes the status of victims, the form and cause of death, the causal mechanism, signs compatible with torture and some circumstances of the facts on the victims. Since the corps were found in wastewater channels, it is not possible to determine the primary scene of the event. Further investigation of these serial killings and deaths must take place, given the aggravated torture evidence.